Modelo para definir índices de corrupción en convocatorias de contratación en Colombia basado en Big Data y procesamiento del lenguaje natural - Luna-Ortega, Julio-César; Cobos-Lozada, Carlos-Alberto; Mendoza-Becerra, Martha-Eliana (Revista Científica, 2023)
This research work proposes a macro-model that allows detecting different probable crimes or anomalies related to corruption in public procurement processes in Colombia. To this effect, the proposed model consists of five main components: 1) specialized services that seek to identify specific situations of probable corruption (three services were proposed: the detection of similarity between documents, the detection of offer manipulation, and the detection of cartels); 2) transversal services that support the transformation of the model into a software tool; 3) additional services where general situations of probable corruption are addressed, specifically the citizen alert service; 4) the explicit relationships between services; and 5) the global output of the model. In the practical experimentation stage, two of the services proposed in this research were put to the test in various scenarios. With the results obtained by some of the classical metrics of the area, the quality of the prediction obtained by the services was determined.